Emergence of A New Entity: The Autoimmune Encephalitis - Ahmad, Q; Ali, MA; Kabir, MA; Alahi, MM; Amin, MP; Kafiluddin, M. (Journal of Medicine, 2012)
Encephalitis has been known as a distinct entity for a long time but its exact cause has remained undetected in about half the cases in spite of extensive investigations. During the last few years there has been reports of cases of encephalitis in which antibodies has been detected against deep grey matter neurons. Antibodies have been detected against the N-methyl-D-aspartate (NMDA) receptors or voltage-gated potassium channels (VGKC). VGKC antibody positive encephalitis usually presents in middle aged or elderly people and is twice as common in men. The main symptoms are memory loss and seizures. Cognitive impairment, confusion, disorientation, personality change and behavioral disturbances are also common. Encephalitis associated with NMDA receptor antibodies is mainly seen in children and young adults, with women being affected about three to four times more often than men. Initially there is a period of cognitive impairment and psychiatric features like hallucinations, agitation and depression but later there is gradual deterioration in conscious level with autonomic features often requiring intensive care. The most striking feature of both these types of encephalitis is their uniform good response to immunomodulating therapies. Intravenous immunoglobulin (IVIG), glucocorticosteroids, plasma exchange and drugs like cyclophosphamide, rituximab, mycophenolate mofetil, azathioprine, singly or in combination have all produced good results. It is this surprisingly easily available effective treatment which makes diagnosis of this condition imperative. Encephalitis is a condition which is encountered by physicians at all levels and so a high level of awareness about the condition will ensure that the condition is not missed. This review about this new condition is being presented to make physicians aware about this devastating but easily treatable disease. DOI: http://dx.doi.org/10.3329/jom.v13i2.12755 J Medicine 2012; 13 : 179-189